2015
DOI: 10.4103/1947-2714.152078
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of frontal sinus and nasal septum patterns as an aid in forensics: A digital radiographic study

Abstract: Background:Skull radiographic examination is a potentially useful procedure for the personal identification in cases where fragments of skull persist with no likelihood of identification based on dental arch.Aims:The study was to determine the uniqueness and reliability of combined frontal sinus (FS) and nasal septum (NS) patterns as observed on posterioanterior (PA) cephalograms for personal identification.Materials and Methods:The randomly selected 149 digital PA cephalograms taken on Kodak 8000C Digital Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 17 publications
6
26
2
7
Order By: Relevance
“…[6,16] Unilateral aplasia was found in 5.7% which was in total contrast with Verma et al as 8.7% and Gopal et al (2016) as 2.5%. [16,17] In the present study, the patterns of NS were observed as straight as 33%, right deviation as 21%, left deviation as 14%, and sigmoid as 33% which was in total contrast with the studies done by David and Saxena as 22%, 42%, 30%, and 2%, respectively, and by Taniguchi et al as 13.4%, 37.6%, 35.3%, and 6.3%, respectively. [4,6] The gender distribution was found to be male dominant in all the patterns of FS and NS except in case of bilateral aplasia in which female dominancy was observed which was in total contrast with the study done by Verma et al where although equal distribution of NS and FS was present except in right dominated asymmetrical FS and Reddy et al where males and females were equally distributed.…”
Section: Discussioncontrasting
confidence: 54%
“…[6,16] Unilateral aplasia was found in 5.7% which was in total contrast with Verma et al as 8.7% and Gopal et al (2016) as 2.5%. [16,17] In the present study, the patterns of NS were observed as straight as 33%, right deviation as 21%, left deviation as 14%, and sigmoid as 33% which was in total contrast with the studies done by David and Saxena as 22%, 42%, 30%, and 2%, respectively, and by Taniguchi et al as 13.4%, 37.6%, 35.3%, and 6.3%, respectively. [4,6] The gender distribution was found to be male dominant in all the patterns of FS and NS except in case of bilateral aplasia in which female dominancy was observed which was in total contrast with the study done by Verma et al where although equal distribution of NS and FS was present except in right dominated asymmetrical FS and Reddy et al where males and females were equally distributed.…”
Section: Discussioncontrasting
confidence: 54%
“…In our study, males and females were equal in number i.e 70 males and 70 females (50% each), which is similar to the studies conducted by Verma K et al (2017) 4 15 . In contrast to these, 150 males and 130 females were taken in study published by Nagarj T (2017) 16 and 74 males and 75 females were enrolled in study published by Verma P et al (2015) 7 . In Cakur B et al (2011) 17 study, 190 males and 220 females were included.…”
Section: Discussionmentioning
confidence: 99%
“…The combined patterns were noted for each radiograph. 7 The results were analyzed using Statistical Package of Social Sciences (SPSS) software version 21. The dimensions of FS between males and females were compared using paired t-test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Неповторимая индивидуальность строения ЛП отмечена многими иссле-дователями [20,22,41,42,[44][45][46][47][48][49], что позволяет прово-дить достоверную идентификацию личности при сравне-нии прижизненной и посмертной рентгенограмм черепа. S. Reddy [45] и P. Verma [42] при комплексной оценке морфометрии перегородки носа и ЛП выявили суще-ственную корреляцию, которая может быть использована для идентификации личности в возрасте старше 20 лет. У мужчин линейные и объемные размеры ЛП больше, чем у женщин, причем преимущественно правая ЛП больше, чем левая, и у мужчин и у женщин.…”
Section: особенности возрастного развития лобных пазухunclassified